YES Bank Fiasco: Arrogance or Negligence. Issue 2 (December 2021) - Akhtar, Shakeb; Alam, Mahfooz; Khan, Mohd Mohsin
The present case study is based on the nation's biggest-ever banking failure of India's fastest-growing private bank, YES Bank. The YES Bank fiasco showcases the prevalent flaws of uprising NPAs and mounting bad debts in the financial sector. Post Asset Quality Review (AQR) conducted by RBI elucidate that the NPA of YES Bank is seven times higher than the actual reported amount in their audit book. The sudden trauma reflected the events unfolding in the bank as the share market plummets drastically and the losses enlarged exponentially. To stymie further deterioration, the Reserve Bank of India (RBI) stepped in and took over YES Bank management. The economy is already set to decelerate to an 11-year low following demonetization and the outbreak threatens to delay a revival in an emerging economy like India. The subject that this case will fit in is Capital Structure, Corporate Governance and Ethics and Auditing.